Sequenciamento de conteúdos nos planejamentos anuais dos professores de química da EJA do ensino médio nas escolas estaduais de São Luís-MA - SAMPAIO, Deusur Gonçalves (2020)
The sequences and the organization of the contents proposed by the educator to address a given curricular component aim to favor a meaningful teaching-learning to the students, in order to provide them to reflect on the applicability of the understood contents. The more the learning content is associated with each other, the greater the ability to be used and understood. The teacher of Youth and Adult Education (EJA), when selecting and organizing its contents, in addition to knowing the basic criteria in the organization of the contents, needs, above all, to know the needs and intentions of its students. The National Common Curricular Base (BNCC) of high school emphasizes that one of the teaching actions to be considered in the curricular organization is the decision on forms of interdisciplinary organization of the curricular components. In this perspective, this research sought to verify the forms of content sequences in the annual plans of high school chemistry teachers in the EJA modality of state schools in the city of São Luís-MA. The methodological approach was based on the qualitative approach, using semi-structured interviews as an instrument for data collection, which was treated by content analysis and organized into “four themes”. In addition to the elaboration of a comparative table showing similarities and differences in the organization and sequences of the chemistry syllabus for High School Education, adopted by the Education Departments of the States of the Northeast Region. The results showed that the choice of content for the Teaching of Chemistry for EJA does not necessarily follow the organizations and sequencing of the official annual didactic plans, since 50% of the interviewed teachers reported that they prepare a personal annual planning according to the real diagnosis of the learning difficulties of her students, emphasizing that they follow the sequences of the contents, however the researcher did not have physical access to these plans. The EJA curriculum needs to be rethought in relation to the content, ordering, relationship between teachers and students in order to achieve meaningful learning for students in this modality. It is also evident, the importance of continuing education not only for teachers but also for managers who work in EJA state schools, since these are fundamental parts in the connection between Supervision of Education of Youth and Adults (SUPEJA) and schools state of Maranhão.